Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.3748/wjg.14.574
|View full text |Cite
|
Sign up to set email alerts
|

Gene modulation associated with inhibition of liver regeneration in hepatitis B virus X transgenic mice

Abstract: biosynthesis (farnesyl diphosphate synthase, Cyp7b1, geranylgeranyl diphosphate synthase, SAA3). CONCLUSION:Our results provide a novel insight into the biological activities of HBx, implicated in the inhibition of liver regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Previous investigations revealed that a number of cellular genes could be downregulated or upregulated by HBx, as indicated by oligonucleotide microarray analysis [12][13][14], which is difficult to be elucidated by the known genetic regulators. Interestingly, several studies have reported a strong correlation between HBV infection and epigenetic alteration of tumor suppressor genes, including p16 [15] and GSPT1 [16], whose expression is frequently downregulated in HCC by hypermethylation.…”
Section: Introductionmentioning
confidence: 98%
“…Previous investigations revealed that a number of cellular genes could be downregulated or upregulated by HBx, as indicated by oligonucleotide microarray analysis [12][13][14], which is difficult to be elucidated by the known genetic regulators. Interestingly, several studies have reported a strong correlation between HBV infection and epigenetic alteration of tumor suppressor genes, including p16 [15] and GSPT1 [16], whose expression is frequently downregulated in HCC by hypermethylation.…”
Section: Introductionmentioning
confidence: 98%
“…As outlined above, HBx could block apoptosis in CLD and via activation of NF-κB. In contrast, when HBx is expressed in normal mouse liver, and such mice are subjected to partial hepatectomy, liver regeneration is largely inhibited [ 58 ]. In the latter case, the levels of free radicals, and corresponding HBx expression and activity are low.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of HBx on the gene expression profile in the regenerated liver after partial hepatectomy of HBx-transgenic mice has been analyzed [ 65 ]. Impaired DNA synthesis and reduction in liver mass in HBx-transgenic mice have been shown to be associated with a weaker expression of genes involved in the cholesterol and nonsterol isoprenoid pathways, as well as serum amyloid A [ 65 ].…”
Section: Hbv Infection and Liver Regenerationmentioning
confidence: 99%
“…The effect of HBx on the gene expression profile in the regenerated liver after partial hepatectomy of HBx-transgenic mice has been analyzed [ 65 ]. Impaired DNA synthesis and reduction in liver mass in HBx-transgenic mice have been shown to be associated with a weaker expression of genes involved in the cholesterol and nonsterol isoprenoid pathways, as well as serum amyloid A [ 65 ]. Moreover, using MALDI imaging MS analysis, we have previously reported that phosphatidylcholine biosynthesis in the regenerating liver is altered by HBV infection, causing a regeneration defect [ 63 ].…”
Section: Hbv Infection and Liver Regenerationmentioning
confidence: 99%